If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(6 + r) = 10 (6 * 8 + r * 8) = 10 (48 + 8r) = 10 Solving 48 + 8r = 10 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-48' to each side of the equation. 48 + -48 + 8r = 10 + -48 Combine like terms: 48 + -48 = 0 0 + 8r = 10 + -48 8r = 10 + -48 Combine like terms: 10 + -48 = -38 8r = -38 Divide each side by '8'. r = -4.75 Simplifying r = -4.75
| x+4=8-4 | | 3x+5400=-12x | | X*x+1=240 | | 15.16+p=15.48 | | 12+12+x+x=16+x-2+16+x-2 | | -270=-6(6n+3) | | 8x-10+4x=-4 | | -5(11-4x)+5(7+x)=11x+10x | | R=-5r+1 | | 10x+6(-9+12x)=11(1+7x) | | 7a-b=15c | | -6(5x+7)=-7x+27 | | -5x+x=25-1 | | 25-7r=8(-5r-1) | | 11r^2+3=25r+8r^2-5 | | -(1+5x)=15-3x | | -(2x+1)=2x-1 | | =4-((14)-11) | | 9=15-k | | 3(x+4)-2(x+5)= | | 9=19x-12 | | 24+2x=28+2x | | -5a/2=-15/4 | | D(t)=12.8-4 | | Y=2x^2+40x+57 | | 428.84=220x+.92 | | K(-1)=-7(-1)+1 | | 6*l=25.2 | | h+8=18 | | -17+3x=-13+3x-4 | | 9x^2-50=0 | | 4+10x+y=6 |